How much are fans willing to pay to help "their" soccer clubs to overcome a crisis? An analysis of central European fans during the COVID-19 pandemic - Petri Lintumäki; Clemens Walcher; Martin Schnitzer (Journal of Risk and Financial Management, 2022)
Through restrictions and people's behavioral changes with regard to public events, the COVID-19 pandemic has had a massive financial impact on professional team sports clubs. Particularly, many smaller clubs that are more dependent on match-day revenues were facing an existential struggle. In this study, we examined the willingness of fans to contribute financially to help their favorite teams to overcome financial difficulties caused by this unforeseen operational risk. Moreover, we investigated the significance of the level of team identification among fans as an antecedent for willingness to pay. Analyzing the data from an online survey with 178 respondents, we found that fans would be willing to participate in fundraising campaigns to support their favorite teams. Among the fans of small clubs, the level of identification drives the willingness to support. On the one hand, the findings are encouraging for clubs as they underscore the potential role fans could play in overcoming the current crisis while showing that including fans in future risk management strategies is a promising approach. On the other hand, for this to be successful, clubs need to unravel and invest in measures for nurturing the fans' identification with the team.
Keywords: 650; COVID-19; crisis management; risk management; professional team sports clubs; sports management; team identification; willingness to pay